Arabidopsis thaliana phytochrome A sensory properties in canopy shade - Philip Prizeman-Green; Marissa Valdivia-Cabrera; Mengke Zhou; Ramon Grima; Karen J. Halliday (Proceedings of the National Academy of Sciences, 2026)
Canopy shade environments can negatively impact plant growth and survival. Phytochrome A (phyA) is essential for seedling adaptation to deep shade, yet its role under moderate natural canopy conditions remains unclear. By expressing a phyA-nanoLUC reporter in Arabidopsis thaliana , we quantify diurnal fluctuations in phyA and its induction by low red to far-red (R:FR) ratio, simulating canopy shade. We uncover a key regulatory function for phyB, which increases phyA stability postdawn in unshaded conditions and modulates expression of PHYA in low R:FR. Further, we demonstrate that beyond its role as a deep shade sensor, phyA is an adept sensor of canopy shade, capable of detecting a range of R:FR ratios across light intensities. Mathematical modeling demonstrates that this property arises from the dynamic features of the phyA High Irradiance Response (HIR) mode of action. Interestingly, phyA synthesis is strongly induced by subtle reductions in R:FR ratio, and is robust to light perturbation, suggesting the phyA-sensory module is configured to detect modest shade. Spectral data from natural shade habitats provide ecological context for our laboratory findings. Physiological analysis indicates that under canopy shade phyA promotes seedling de-etiolation, organizes resource management, and accelerates reproductive development. We propose that this suite of responses, termed the “canopy adaptation strategy,” enhances survival chances under conditions where shade avoidance strategies are maladaptive.